Fall Prevention - Kristen D. Smith (EDIS)
Older adults tend to fall more often than other people. There are several reasons why: physical, behavioral and mental changes associated with aging, lifestyle and daily behaviors, environmental factors, and community policy. In this document we will discuss each of these risk factors. Then, we will take a look at how older adults can reduce the risk of falling. This document is FCS2214 FY629, one of a series of publications from the distance education in-service "Aging in the 21st Century." First published: September 2003.